2016
DOI: 10.1111/inr.12316
|View full text |Cite
|
Sign up to set email alerts
|

Disaster nursing experiences of Chinese nurses responding to the Sichuan Ya'an earthquake

Abstract: Hospital and nursing leaders should provide disaster training opportunities that included topics such as compiling resource inventories, formulating disaster drills and simulations, managing emergencies, and using emergency communication methods. Health policy-makers should be required to prioritize capacity-building training for front-line nurses as well as to develop and implement disaster management plans to better prepare nurses for future disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…Here, this study result shows a parallelism with other studies (Al Thobaity et al 2017;Celik 2010;Diab & Mabrouk 2015;Li et al 2017;Ozcan 2013;Wenji et al 2015). Although international nursing organizations warn nurses to be prepared for disasters, as in many countries, nurses' training for disasters in Turkey is inadequate (Rokkas et al 2014;Taskiran & Baykal 2017) because, there is no standardized, accessible and continuous disaster education in the undergraduate curricula and hospitals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here, this study result shows a parallelism with other studies (Al Thobaity et al 2017;Celik 2010;Diab & Mabrouk 2015;Li et al 2017;Ozcan 2013;Wenji et al 2015). Although international nursing organizations warn nurses to be prepared for disasters, as in many countries, nurses' training for disasters in Turkey is inadequate (Rokkas et al 2014;Taskiran & Baykal 2017) because, there is no standardized, accessible and continuous disaster education in the undergraduate curricula and hospitals.…”
Section: Discussionsupporting
confidence: 85%
“…Nurses' experiences, opinions and training needs regarding disasters were investigated, and their perceptions of disaster preparedness and core competencies were measured. Like previous studies, most nurses reported they had no prior disaster experience and disaster response experience (Baack & Alfred 2013;Celik 2010;Hodge et al 2017;Labrague et al 2016;Li et al 2017;Ozcan 2013;Usher et al 2015). Moreover, Rizqillah & Suna (2018) found that 58.3% of nurses had previous disaster experience and 56.7% of nurses had disaster response experience.…”
Section: Discussionsupporting
confidence: 58%
“…However, these studies lacked long-term follow-up results, did not use controlled groups, and required considerable resources to prepare (Alim, Kawabata, & Takanawa, 2015;Jung et al, 2016;Pesiridis, Sourtzi, Galanis, & Kalokairinou, 2015), such as using a high fidelity human mannequin simulator or patient simulator for practicing CPR (cardiopulmonary resuscitation) and other treatment, as well as actorpatients who were dressed and made up using artificial wounds and blood so as to mimic a "real"-life case situation. Few training program has been developed in a systematic manner, even though there is an increasing demand in China (Li et al, 2017).…”
mentioning
confidence: 99%
“…Another study by Li et al on Sichuan earthquake in China, they pointed to the lack of collaboration among disaster relief teams and insu cient leadership. [18].Apparently, one of the challenges of modern age, given the type of disasters, is the necessity of an integrated system to face disasters.…”
Section: Discussionmentioning
confidence: 99%